The Effect of Cultural Values on Business Strategy Choices - Valencia. S. Permata, Antonius. S. Setiawan, Johan. G. Ony, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The strategy is important in the effort to achieve firm performance. The decision of an entrepreneur in determining the choice of strategy is often influenced by certain factors. Ethnic cultural values embraced by an entrepreneur will often be an important issue that will have an impact on the choice of their business strategy. Ã‚Â Therefore, this study aims to examine the effect of cultural values on business strategy choices. The study was conducted using quantitative methods using primary data through a survey on micro, small and medium business entrepreneurs in Palembang city. A total of 150 questionnaires were distributed to entrepreneurs. The number of questionnaires used in this study was 107 (71%). Structural Equation Modeling (SEM) Partial Least Squares (PLS) analysis using Warp PLS version 5.0 software is used to test the hypothesis. The results of the study indicate that the cultural values embraced by entrepreneurs influence the choice of business strategies that they implement.